Notch signaling coordinates cellular proliferation with differentiation during zebrafish fin regeneration - Grotek, Bartholomaeus; Wehner, Daniel; Weidinger, Gilbert (Development (Cambridge, England), 2013)
Zebrafish can completely regenerate amputated fins via formation of a blastema, a proliferative mass of undifferentiated precursor cells. During regenerative growth, blastema proliferation must be tightly coordinated with cellular differentiation, but little is known about how this is achieved. Here, we show that Notch signaling is essential for maintenance of blastema cells in a proliferative undifferentiated state. We found that the Notch pathway is activated in response to fin amputation in the highly proliferative region of the blastema. Chemical interference with Notch signaling resulted in a complete block of regeneration. Notch signaling was not required for the earliest known cellular processes during blastema formation, i.e. dedifferentiation and migration of osteoblasts, but specifically interfered with proliferation of blastema cells. Interestingly, overactivation of the pathway via misexpression of the intracellular domain of the Notch receptor (NICD) likewise inhibited regenerative outgrowth. In NICD-overexpressing fins, overall blastemal cell proliferation was not enhanced, but expanded into proximal regions where cellular differentiation normally occurs. Similarly, blastemal and epidermal gene expression territories invaded proximal regions upon sustained Notch activation. Concomitantly, NICD overexpression suppressed differentiation of osteoblasts and caused an expansion of the undifferentiated blastema. Together, these data suggest that Notch signaling activity maintains blastemal cells in a proliferative state and thus coordinates proliferation with differentiation during regenerative growth. © 2013. Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Blastema; Caudal fin; LY411575; Notch; Osteoblasts; Regeneration; Zebrafish